P28 Unloading reaction alterations in patients with functional ankle instability? - Jain, TK; Wauneka, CN; Liu, W (British journal of sports medicine, 2017)
Study DesignExploratory design.ObjectivesTo assess the ‘unloading reaction’ in patients with functional ankle instability (FAI) in a laboratory setting.BackgroundAnkle giving-way or feelings of ankle instability after a lateral ankle sprain is a key component in the diagnosis of functional ankle instability (FAI). However, the aetiology of ankle giving-way phenomenon remains unclear.Methods and MeasuresWe studied the unloading reaction in 24 subjects with unilateral FAI (65% females; mean age: 34.2±7.7 years) recruited from the community. A trapdoor device with a tilt platform causing sudden 30° ankle supination was used to test both ankles in random order on two different days three days apart. The first five trials of sudden trapdoor drop occurred without nociceptive electrical stimulation (‘no stim’) followed by five trials of the combined trapdoor drop with nociceptive stimulation (‘with stim’). Unloading reaction was quantified by recording the maximal reduction in total body weight (RBW) using the two force platforms at least 0.5 s after the trapdoor release. Paired samples t-test was used to determine between-ankle and testing condition differences in the average RBW. The significance level was set at 0.05.ResultsThe averaged RBW in the injured ankles was 120.6±188.0 n under ‘with stim’ condition, which was significantly greater (p<0.05) than 61.9±69.5 n (uninjured ankles, ‘with stim’), 57.6±52.3 n (injured ankles, ‘no stim’), and 54.5±55.1 n (uninjured ankles, ‘no stim’), respectively. The recorded videos demonstrated drastic responses in five subjects hanging their weight on the safety harness when tested with ‘with stim’ on the injured ankles, duplicating an ankle giving-way episode. No harm was noted during the testing.ConclusionThis study demonstrates significant increase in unloading reaction on the injured ankles when tested under sudden ankle stretch and nociceptive stimulation. This finding may help to understand the aetiology of ankle giving way.